Evidence for high saturation of porous amorphous carbon films by noble gases - Krainyukova, N.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Results of the electron diffraction study of Kr and Xe deposits on amorphous porous carbon substrates are reported. We have observed mixtures of crystallites typical of condensates formed at such substrates at low deposition temperatures. However, in the warming process at temperatures about three-to-five degrees below the sublimation point characteristic of flat substrates, the diffraction patterns demonstrate that large crystallites gradually disappear and a highly disordered matter forms. Such transformed samples are kept insidesubstrates several dozens degrees above the sublimation points which are typical of these substances at flat (e.g. metallic) substrates.We ascribe these features to specificity of composites formed from noble gases strongly bonded inside porous carbon matrices due to capillary filling at temperatures close to the sublimation points.